Chronic cerebral hypoperfusion causes decrease of O-GlcNAcylation, hyperphosphorylation of tau and behavioral deficits in mice - Zhao, Yang; Gu, Jin-hua; Dai, Chun-ling; Liu, Qun; Iqbal, Khalid; Liu, Fei; GONG, CHENG-XIN (Frontiers in Aging Neuroscience, 2014)
Chronic cerebral hypoperfusion (CCH) is one of the causes of vascular dementia (VaD) and is also an etiological factor for Alzheimer's disease (AD). However, how CCH causes cognitive impairment and contributes to Alzheimer’s pathology is poorly understood. Here we produced a mouse model of CCH by unilateral common carotid artery occlusion (UCCAO) and studied the behavioral changes and brain abnormalities in mice 2.5 months after UCCAO. We found that CCH caused significant short-term memory deficits and mild long-term spatial memory impairment, as well as decreased level of protein O-GlcNAcylation, increased level of tau phosphorylation, dysregulated synaptic proteins and insulin signaling, and selective neurodegeneration in the brain. These findings provide mechanistic insight into the effects of CCH on memory and cognition and the likely link between AD and VaD.